Entrepreneurial Management Coastal Muslim In The Village Bongo Gorontalo - Rahmat, Abdul (Universitas Islam Negeri Raden Intan Lampung, 2017)
The aim of this research activities to proving the entrepreneurial management of the coastal Muslim community in the village of Bongo. Experimental design used in this research is quasi experiment with the design of